REMEDIAL APPLICATIONS OF SILENCING RIBONUCLEIC ACIDS AND MODALITIES FOR ITS DELIVERY TO THE KIDNEYS - A REVIEW - Wang, Dongjie; Lv, Yanfen; Zhu, Huifang; Lv, Guifeng; Huang, Jiyi (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: The Kidney has been the target organ for the delivery of silencing ribonucleic acids (silencing RNA) administered systemically in comparison to other body tissues. Materials and method: In this review, we discussed different approaches made to delivering proteins to the kidneys in different conditions like normal and pathological defects. Data from clinical experiments have been used to discuss and support the administration of silencing RNA for the treatment of kidney diseases. Results: Results were achieved using the available genome wide RNA libraries. Conclusion: The research results are helpful in application to 3D and conventional models to find the involvement of signal pathways in kidney diseases.